On Limit Cycles of Planar Dynamical System Via Dulac- Cherkas Function - Amen, Azad Ibrahim (Sulaimani Journal for Pure and Applied Sciences, 2015)
The main aim of this paper is to construct Bendixson-Dulac and Dulac-Cherkas functions to study the maximum number of limit cycles for several families of planar dynamical system. We also apply the results to Lienard and biochemistry reaction systems.
Keywords: Limit cycles Bendixson function DulacCherkas function planar vector field